Laval Virtual Doctoral Consortium Proceedings - Richir, Simon (International Journal of Virtual Reality, 2025)
The document hereby presents the proceedings of the Laval Virtual Doctoral Consortium, which took place in Laval on 10 April 2025. We would like to thank the authors, as well as the reviewers for their contributions. This is an International Journal of Virtual Reality (IJVR) special issue.